Impurity distribution in metallic dysprosium during distillation purification - 张小伟 苗睿瑛 李传军 吴道高 闫缓 王志强 陈德宏 颜世宏 李宗安 (Journal of rare earths, 2016)
The distribution rules of impurities contents in distilled metallic dysprosium were researched, and a theoretical analysis was carried out. The research results indicated that, the content of impurity in distilled metal, such as Al and Fe, was lower in the ini-tial stage, increased slowly in the middle stage, and increased rapidly in the last stage during the process of distillation purification. The calculated method of separation coefficient of impurity in crude metal by content of impurity in distilled metal was not suitable for high pure metals, and the modified separation coefficient was proposed, and it equaled 1/6.1 and 1/16.9 for impurity Al and Fe. The physical process of distillation was coincident with that of solidification essentially, and solute re-distribution theory in solidify-ing front could be used to describe the impurity distribution near evaporating surface. In the former stage of distillation purification, the diffusion of impurity in liquid metal could reach a quasi-equilibrium state, the calculated result of impurity content in distilled metal agreed well with experiments. In the latter stage of distillation process, the diffusion rate of impurity in liquid metal decreased, and the content in distilled metal was larger than the calculated result.